2016
DOI: 10.1111/tbj.12603
|View full text |Cite
|
Sign up to set email alerts
|

Kimura Disease of the Breast - A Previously Undescribed Entity

Abstract: Kimura disease (KD) is a rare chronic inflammatory disorder of unknown etiology, primarily seen in young Asian males. The disease is characterized by a triad of painless subcutaneous masses in the head and neck region, blood and tissue eosinophilia, and elevated serum immunoglobulin E levels. We report an unusual case of a 40-year-old woman found to have KD of the breast which presented clinically as carcinoma, leading to a diagnostic dilemma. To the best of our knowledge, this is the first case of KD in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Kimura disease is a rare chronic inflammatory disease of unknown origin, first described by Kimura et al in 1948 1 . To date, there have only been 200 reported incidences of Kimura disease globally, 2 and only 1 reported case of Kimura Disease of the Breast in 2016 3 . Kimura disease predominantly occurs in Asian male populations, with incidence peaking around the second and third decade of life 4,5 …”
Section: Discussionmentioning
confidence: 99%
“…Kimura disease is a rare chronic inflammatory disease of unknown origin, first described by Kimura et al in 1948 1 . To date, there have only been 200 reported incidences of Kimura disease globally, 2 and only 1 reported case of Kimura Disease of the Breast in 2016 3 . Kimura disease predominantly occurs in Asian male populations, with incidence peaking around the second and third decade of life 4,5 …”
Section: Discussionmentioning
confidence: 99%
“… 1 Breast, as observed in our patient, is an unusual location for disease involvement and, to the best of our knowledge, the first case of KD in the breast was published in the medical literature in 2016 by Kakkar et al who reported a 40-year-old female with breast KD presented with painful breast lump and axillary lymphadenopathy. 3 Later in 2020, another case report described a case of KD of the breast in a 50-year-old Asian female, which had bilateral multifocal breasts masses and bilateral axillary lymphadenopathy. 4 In comparison to the previously reported cases, the distinct presentation of our patient was painless diffuse breast enlargement and axillary lymphadenopathy without palpable breast mass or focal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the head and neck, cases with axillary lymph node and breast involvement have also been reported. 15,16 More extensive patterns of disease should prompt consideration of an alternative diagnosis. The key is to follow the clinical course with a low threshold for extensive work up to rule out malignancy in patients who show clinical progression.…”
Section: Discussionmentioning
confidence: 99%